Edukasi Pembatasan Asupan Gula, Garam Lemak dalam Pemilihan Jajanan Remaja - Isniati Dwijayanti; Dessy Aryanti Utami; Maya Fernandya Siahaan; Muthia Farah Diba (Lembaga Pengembangan Kinerja Dosen, 2025)
Non-communicable diseases (NCDs) have been the leading cause of death in Indonesia for the past 19 years. This is due to a change in a diet high in sugar, salt and fat (SSF). Adolescents are one of the groups of people who often consume high snacks (SSF). It is feared that this will cause NCDs in the future. The purpose of this activity is to provide education with the theme of SSF Intake Restrictions in the Selection of Adolescent Snacks which is expected to increase knowledge and awareness of the target of SSF intake and avoid the target of the risk of NCDs. Nutrition education is carried out offline using the lecture method, providing e-booklets, questions and answers, and implementing pre-test and post-test using google form. The educational participants were attended by 85 students from 35 North Jakarta State High School. The results of nutrition education have a positive impact on the target knowledge level which is characterized by an increase in post-test scores on each component of the question